RANCANGAN SIMULASI APPRAOCH LIGHTING SYSTEM BANDAR UDARA MENGGUNAKAN MICROSOFT VISUAL STUDIO 2015 DI SEKOLAH TINGGI PENERBANGAN INDONESIA - Muhammad Fajar; Zulina Kurniawati; Agus Herianto (Langit Biru: Jurnal Ilmiah Aviasi, 2019)
At this time cadets experienced some problems in the implementation of practice in Airfield Lighting System subject, due to the props that can not be used properly. The designed Approach Lighting System Simulation is intended as one solution to the problem, and it is a new idea to be used in practical activities, especially regarding to the Approach Lighting System configuration. This simulation design was created using Microsoft Visual Studio 2105 programming language where its result will be able to describe some configuration of Approach Ligthing System. In the end the authors hope this simulation design can provide benefits in the enrichment of subject matter practice materials in Airfield Lighting System course of Airport Electrical Engineering, Department of Aviation Engineerring, Indonesian Civil Aviation Institute. It is also suggested that the application programming language Microsoft Visual Studio 2015 can be developed further in designing learning simulations for other subjects in the Airfield Lighting System subject.